Teaching and learning process to enhance teaching effectiveness: a literature review - Afzal Sayed Munna; Md Abul Kalam (International Journal of Humanities and Innovation (IJHI), 2021)
Teaching and learning process can be defined as a transformation process of knowledge from teachers to students. It is referred as the combination of various elements within the process where an educator identifies and establish the learning objectives and develop teaching resources and implement the teaching and learning strategy. On the other hand, learning is a cardinal factor that a teacher must consider while teaching students. The paper evaluated various academic journals, pedagogy, and inclusive practices to assess the teaching effectiveness within the higher education setting. The objective of the research is to assess the teaching effectiveness in a higher education setting. The research used experimental research methods (primarily reflection) using literary forms to analyse the theory with the reinforcement of the practice from the university experiences. The research findings suggest that providing positive and adequate formative and developmental feedback, introduction of role-play has a profound positive impact on the students' confidence and self-esteem. It was also revealed that, active learning environment promotes inclusivity and improve the faculty and student academic performances. The research findings will enable the educators to help create and implement an inclusive teaching and learning environment to improve the learner’s expectation and academic performance.